Civics Teachers' Strategies in Instilling Pancasila Values Through Contextual Learning at MIN 1 Tuban - Nur Laili Dina Hafni; Nur Asri Fitri Rahmawati Ningtias; Siti Nur Ika Salsabila; Moch Raja Al Afwu (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to describe the strategies employed by Civic Education teachers in instilling Pancasila values through contextual learning at MIN 1 Tuban. The research employed a qualitative descriptive approach. Data were collected through observations, in-depth interviews, and documentation involving Civic Education teachers, the school principal, and students. Data validity was ensured through source and technique triangulation, while data were analyzed using the Miles, Huberman, and Saldaña model, which includes data condensation, data display, and conclusion drawing and verification. The findings reveal that teachers integrate Pancasila values into lesson planning, implementation, and assessment by connecting learning materials with students' real-life experiences. The implementation is supported by teachers' role modeling, a positive school culture, active learning methods, and students' active participation in the learning process. Although several challenges were identified, including limited instructional time, differences in students' characteristics, and the influence of technological developments, contextual learning proved effective in strengthening students' understanding, attitudes, and behaviors that reflect Pancasila values.